2018
DOI: 10.1186/s13104-018-3401-y
|View full text |Cite
|
Sign up to set email alerts
|

Associations between endothelial progenitor cells, clinical characteristics and coronary restenosis in patients undergoing percutaneous coronary artery intervention

Abstract: ObjectiveEndothelial progenitor cells (EPCs) are produced in the bone marrow and mobilized to the peripheral blood playing a key role in endothelial repair. The objective of this study was to evaluate circulating EPC before and after percutaneous coronary intervention (PCI) with stent implantation and their associations with coronary restenosis and adverse cardiovascular events. Venous blood was obtained before and the day after PCI. Quantification of total white blood count and identification of EPCs (CD45−CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Our results display a strong clinical significance. The dysfunction of EPCs represents the starting step, as well as a primary factor in the dismal angiogenesis of CAD [39,40]. Clearly, our findings show that the dysfunctional properties of EPCs are associated with CAD, suggesting that CAD negatively affects the maintenance of vascular homeostasis.…”
Section: Discussionmentioning
confidence: 64%
“…Our results display a strong clinical significance. The dysfunction of EPCs represents the starting step, as well as a primary factor in the dismal angiogenesis of CAD [39,40]. Clearly, our findings show that the dysfunctional properties of EPCs are associated with CAD, suggesting that CAD negatively affects the maintenance of vascular homeostasis.…”
Section: Discussionmentioning
confidence: 64%
“…In addition to their relevance in sprouting angiogenesis, EPC circulation, mobilization, and differentiation also play an essential role in the repair of injured vessels [4][5][6]. In recent years, the role of EPCs in the renewal of ECs integrity and function has gained attention from the scientific community, in particular, from the field of ischemia and cardiovascular disorders, opening new therapeutic perspectives for patient treatments [45][46][47]. So far, the lack of a precise panel of cell surface markers drives some heterogeneity in the methodologies used for EPCs identification.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Montenegro et al no significant association between PC counts (defined as CD45− CD34+ CD31+ CD133/2+ CD309+ cells) and the incidence of restenosis was evident, even though there was a trend towards higher PC counts before and after PCI in patients who would later develop restenosis. In this study, a decrease in PC counts was observed in two-thirds of the patients [73]. The size of the study (n = 37) might, however, limit the capacity of this study to detect differences.…”
Section: Progenitor Cells Counts and Outcome After Stentingmentioning
confidence: 62%